NILAI-NILAI KEARIFAN LOKAL PADA UNGKAPAN TRADISIONAL UPACARA PERNIKAHAN MASYARAKAT DESA REMBAN KABUPATEN MURATARA PROVINSI SUMATERA SELATAN - Mega Ardiati; Sainil Amral; Ade Rahima (Universitas Batanghari, 2019)
The purpose of this research is to describe (1) the values of local genius on the traditional custom expressions in the stage pre-marriage of the society in Remban Muratara District Sumsel Province; (2) The values of local genius on the traditional custom expressions in the stage of the wedding day of the society in Remban Muratara Regency Sumsel Province; (3) The values of local genius on the traditional custom expressions in the stage of post-marriage in Remban District Muratara Sumsel province. This type of research is qualitative descriptive. The data in this research is the traditional custom expressions of marriage ceremony. The is data analyzed by using content analysis technique. Based on the analysis of the data, it shows that : (1) Local genius values in the aspect of courtesy norms on traditional custom expressions in the stage of pre-marriage in Remban Muratara Sumsel is politeness norm which can bes seen from the expression man di kami segalo jadi, kalu di kawan bukan saot, (2) The values of local genius in the aspect of politeness norms on traditional custom expressions of the wedding day in Remban District Muratara Sumsel province is modesty norm which can be seen in the expression tepak ko betando kami menepati janji, and (3) the values of local genius in the aspect of politeness values of the traditional custom expression in the stage of post-marriage in Remban Muratara Regency of Sumsel Province is modesty which can be seen in the expression kami menabor beras kunyit, selamatan hidup sampai mati.